Perceptions of the police and perceived police legitimacy within a sample of young adults in Iceland - Tinna Kristín Indíana Kristinsdóttir 2000- (2022)
Public support toward the police and coopeation is a crucial component for the police to be successful in maintaining law and order in a society. Furthermore, the police depend on the public to obey the law, report crimes, provide information and help identify offenders. Therefore, it is important to ensure positive views of the police and voluntary compliance among the public. This study examined trust and perceptions toward the police within a sample of young adults, aged 18-25, in Iceland. Previous research strongly indicates that youths and young adults have less favorable views of the police than older individuals and that crime reporting has a positive correlation with victims’ trust and satisfaction with the police. Results did not show significant correlations between either age or gender and perceptions of the police. Additionally, perceptions of the police were not found to be affected by whether young adults reported offences to the police. However, participants’ perceived accessibility to the police, previous experiences of violent offences and perceived views of others toward the police had a positive significant correlation with participants’ perceptions of the police. Perceptions of the police were more positive among those who had not experienced a violent offence. Stuðningur og samstarfsvilji almennings eru mikilvægir þættir svo að lögregla geti sinnt því hlutverki sínu að halda uppi lögum og reglu í samfélaginu. Lögreglan stólar á almenning til þess að fylgja lögum, tilkynna afbrot, veita upplýsingar og aðstoða við að bera kennsl á afbrotamenn. Af þessum ástæðum er mikilvægt að tryggja að almenningur hafi jákvæð viðhorf til lögreglu og vilji fylgja fyrirmælum hennar. Þessi rannsókn skoðaði traust og viðhorf gagnvart lögreglu í úrtaki af ungu fólki á aldursbilinu 18-25 ára á Íslandi. Niðurstöður fyrri rannsókna hafa sýnt fram á að ungt fólk hefur neikvæðari viðhorf til lögreglu heldur en fólk sem er komið lengra inn á fullorðinsaldur og að það að tilkynna brot hefur jákvæða fylgni við traust ...